Physiotherapy In The Management Of Musculoskeletal Disorders: A Systematic Review (The Review of Diabetic Studies, 2025)
Musculoskeletal disorders (MSDs) are among the leading causes of pain, disability, and reduced quality of life worldwide, placing a significant burden on healthcare systems and economies. Physiotherapy has been widely recognized as a central component in the management of MSDs, offering non-invasive and cost-effective interventions aimed at improving function, reducing pain, and enhancing overall well-being. This systematic review synthesizes current evidence on the effectiveness of physiotherapy in the management of common musculoskeletal conditions, including low back pain, osteoarthritis, neck pain, and shoulder disorders. Electronic databases such as PubMed, Scopus, and Web of Science were searched for peer-reviewed studies published in the past ten years. Inclusion criteria comprised randomized controlled trials, cohort studies, and systematic reviews that evaluated physiotherapy interventions such as therapeutic exercise, manual therapy, electrotherapy, and patient education. Findings indicate that structured exercise therapy and patient-centered education are consistently effective in reducing pain and disability, while manual therapy and adjunct modalities provide additional short- to medium-term benefits. Multimodal physiotherapy programs, when tailored to individual patient needs, demonstrated superior outcomes compared to isolated interventions. However, heterogeneity in study designs, outcome measures, and intervention protocols limits comparability across studies. This review highlights the essential role of physiotherapy in MSD management, underscores the importance of individualized, evidence-based approaches, and calls for further high-quality research to establish standardized treatment guidelines.